Analisa Klorin Pada Beras yang Beredar di Pasar Induk Jakabaring Kota Palembang 2023 - Muslimin, Muslimin; Sigalingging, J; Susiyanti, Susiyanti; Primasari, Anggia; Irzanita, Irzanita; Freska, Ferry (JURNAL KESEHATAN TERAPAN, 2024)
This research aims to carry out chlorine analysis in rice circulating at the Jakabaring Main Market, Palembang City, in 2023. Chlorine, a chemical element that is generally used as a disinfectant, has the potential to become a contaminant in rice that can affect human health if it is present in excessive amounts. . With the Jakabaring Main Market as the focus of the research, we collected rice samples from various producers to analyze the chlorine content and identify potential sources of contamination. The analytical method involves the use of Qualitative Method techniques, to determine the chlorine concentration in the rice samples. rice processing from producers was also collected to understand potential sources of chlorine. It is hoped that the results of this research will provide an in-depth understanding of the level of chlorine contamination in rice at the Jakabaring Main Market, as well as identifying factors that contribute to this contamination. These findings can provide a basis for manufacturers, governments and food regulatory authorities to take necessary actions to improve food safety and public health